Study of functional outcome of free flap reconstruction in oral cavity malignancies - Modi, Devanshi B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Oral cavity squamous cell carcinoma are likely to be associated with occult nodal metastasis at presentation so diagnosis is usually late when the disease has already reached an advanced stage, for this reason, neoplasm dimensions of clear margins needs be at least 1 cm around the tumour, which leads to large resections requiring reconstructive surgery with important functional outcomes. The aim can be achieved with the use of micro vascular free flaps that have replaced regional flaps to ensure better functional and aesthetic results. Methods: A total of 100 patients with oral cavity malignancies were assessed for the functional outcome of cosmoses, speech and swallowing and were compared for each flap using the Fischer’s test. Follow up was done at 3 and 6 months after completion of curative treatment. Results: The failure rate of free fibular flap was 48% which is higher than ALT (18%) and FRAFF (22%). Functional outcome of cosmetic (p=0.38), speech (p=0.58) and swallowing (p=0.10) with pedicle was not as good as free flap for cases of buccal mucosa after failure with free flap. Conclusions: In carcinoma of buccal mucosa and tongue free flaps offered better functional outcome in terms of cosmesis, speech and swallowing compared to pedicled flaps.